Inspection and appraisal of old buildings: building defect reports for the rehabilitation process - Vicente, R. (2012)
The increasing concern and knowledge on architectural heritage have been, in the recent decades, serious reasons for urban rehabilitation and renovation processes. There are many strategies and methods to systematize various tasks in a city renovation process, which efficiency depends mainly on the type of buildings (structural schemes and techniques, type of construction materials), on the type of global project approach (singular buildings, groups of buildings, urban intervention zones, etc.) and on the exact final purpose (risk assessment and decision making, future rehabilitation projects, definition of a council maintenance policy, etc.). In what concerns large renovation programs of old city centres, choosing the most adequate approach for inspection, appraisal and diagnosis is a complex task that can determine the success or the total failure of the project purpose. This paper describes the procedure used for the inspection of 700 buildings located in the old city centre of Coimbra (Portugal). A complete identification and inspection survey was carried out for all of the buildings on three different domains: (a) architectural typologies, (b) constructive typology, building defects, conservation state, and (c) socio-demographic characterization. All the data gathered was recorded for each building and connected with a SIG application, as well as with a relational database, in order to have a deeper and interdisciplinary knowledge of the project perimeter and hence to be able to manage the historical building stock. In this paper will be presented the building check-lists developed for inspection, the building defect reports produced for the rehabilitation and renewal process. It will be presented the overall results from the inspection survey for different construction elements that allowed the characterization of traditional construction solutions and diagnosis of the most common defects for these type of buildings.